Development and biopharmaceutical evaluation of osmotic pump tablets for controlled delivery of diclofenac sodium - Rani M.; Surana R.; Sankar C.; Mishra B. (My University, 2025)
Based on the principles of an elementary osmotic pump (OP), OP tablets were designed and evaluated with the aim to deliver diclofenac sodium (DS) in a controlled manner. In vitro evaluation was done in various release media and kinetics was evaluated using the regression coefficient analysis. Effects of orifice size, coating membrane type, coating thickness, static and stirred conditions and pH variation were studied. In vivo evaluation was performed on six healthy human volunteers and various pharmacokinetic parameters (C max, tmax, AUC0-24, MRT) and relative bioavailability were calculated. The results were compared with the performance of two commercial tablets of DS. The drug release from OP tablets was dependent on the type and thickness of the coating membrane, but was independent of the orifice size and static and stirred conditions of the release medium. The OP tablets provided a prolonged and controlled DS release compared to commercial sustained-release and conventional tablets of DS.